Car-T Treatment for Hematological Malignancies. (June 2020) - Atrash, Shebli; Bano, Kulsum; Harrison, Bradley; Abdallah, Al-Ola
Chimeric antigen receptor (CAR)-T-cell therapy has sparked a wave of optimism in hematological malignancies, reflected by the successful results of early clinical trials involving patients with pre-B-cell acute lymphoblastic leukemia, B-cell lymphomas and multiple myeloma. CAR-T-cell therapy is considered to be a novel immunotherapy treatment that has the potential for curing certain hematological cancers. However, as use of CAR-T-cell therapy has grown, new challenges have surfaced. These challenges include the process of manufacturing the CAR-T cells, the mechanisms of resistance that underlie disease relapse, adverse effects and cost. This review describes the published results of clinical trials and expected developments to overcome CAR-T resistance.